Patient empowerment and general self-efficacy in patients with coronary heart disease: a cross-sectional study - Anita Kärner Köhler; Pia Tingström; Tiny Jaarsma; Staffan Nilsson (BMC Family Practice, 2018)
Abstract Background In managing a life with coronary heart disease and the possibility of planning and following a rehabilitation plan, patients’ empowerment and self-efficacy are considered important. However, currently there is limited data on levels of empowerment among patients with coronary heart disease, and demographic and clinical characteristics associated with patient empowerment are not known. The purpose of this study was to assess the level of patient empowerment and general self-efficacy in patients six to 12 months after the cardiac event. We also aimed to explore the relationship between patient empowerment, general self-efficacy and other related factors such as quality of life and demographic variables. Methods A sample of 157 cardiac patients (78% male; age 68 ± 8.5 years) was recruited from a Swedish hospital. Patient empowerment was assessed using the SWE-CES-10. Additional data was collected on general self-efficacy and well-being (EQ5D and Ladder of Life). Demographic and clinical variables were collected from medical records and interviews. Results The mean levels of patient empowerment and general self-efficacy on a 0–4 scale were 3.69 (±0.54) and 3.13 (±0.52) respectively, and the relationship between patient empowerment and general self-efficacy was weak (r = 0.38). In a simple linear regression, patient empowerment and general self-efficacy were significantly correlated with marital status, current self-rated health and future well-being. Multiple linear regressions on patient empowerment (Model 1) and general self-efficacy (Model 2) showed an independent significant association between patient empowerment and current self-rated health. General self-efficacy was not independently associated with any of the variables. Conclusions Patients with a diagnosis of coronary heart disease reported high levels of empowerment and general self-efficacy at six to 12 months after the event. Clinical and demographic variables were not independently associated with empowerment or low general self-efficacy. Patient empowerment and general self-efficacy were not mutually interchangeable, and therefore both need to be measured when planning for secondary prevention in primary health care. Trial registration NCT01462799.